HIGHER EDUCATION FINANCING MODEL IN UKRAINE: CHANGE OF PRIORITIES - KYRYLENKO, Olga; ZHADAN, Olena (Scientific journal «World of Finance», 2023)
Introduction. Higher education is always one of the most important priorities of social development. In the Strategy for the Development of Higher Education in Ukraine for 2022-2032, it is noted that Ukraine has an ineffective system of higher education, which, first of all, is due to insufficient funding of the industry. The long-term model of financing higher education had a number of systemic flaws and therefore proved to be ineffective, which complicated the process of training modern specialists. Institutions of higher education in the country constantly experience a lack of financial resources to ensure full-fledged current functioning; most of them have practically no funds for the development of their own material and technical base, stimulation of better results of the work of the teaching staff, participation in educational and scientific international cooperation. Solving these problems requires the introduction of new approaches to the process of financial provision of higher education institutions.The purpose of the article is track the change in priorities in financing higher education, compare the financing models of higher education institutions used in Ukraine, determine their shortcomings and advantages, justify proposals for improving the current model of budgetary financing of higher education institutions, taking into account the best foreign practices.Results. The data on the distribution of higher education financing volumes among their sources in the countries that are part of the Organization for Economic Cooperation and Development are presented; the dynamics of the share of expenditures on higher education from the state budget of Ukraine in expenditures on education and aggregate expenditures of the state budget, as well as in GDP. A conclusion was made regarding the insufficient amount of funding in the field of education. Approaches to determining the content and financing mechanisms of higher education are analyzed. The change of priorities in the financing of higher education in Ukraine is tracked, the main shortcomings and advantages of the used financing models are highlighted. Suggestions for improving the current formulaic model of budget financing of higher education institutions, taking into account the best foreign practice, have been formulated.Conclusions. Financing of higher education directly affects the efficiency of the industry and the achievement of strategic guidelines for its development. In the conditions of martial law, the issue of financial support becomes particularly acute and urgent due to the acute shortage of budgetary resources. It is noted that the model of financing higher education institutions should be clear, transparent and diversified, and state financing should be based on a formulaic approach that takes into account the final results of higher education. It is proposed to supplement the formula for the distribution of state budget expenditures on higher education among institutions of higher education with indicators grouped according to the following directions: financial environment, academic environment, technology and innovation, student dormitories. Emphasis is placed on the need for a real implementation of the principle of financial autonomy of Ukrainian universities, which includes, in particular, the diversification of financial resources and the broad involvement of alternative sources.